The Zoonotic Potential of Fungal Pathogens: Another Dimension of the One Health Approach - Reetu Kundu; Yashik Bansal; Nidhi Singla (Diagnostics, 2024)
Zoonotic diseases are caused by viruses, bacteria, fungi and parasites and they comprise about 75% of all emerging infectious diseases. These can be transmitted via the direct (scratches on skin or animal bites) or indirect mode (through environmental shedding of infectious agent by the infected animal) of transmission. Environmental changes, whether in the form of urbanization, industrialization or destruction of wildlife habitats, lead to more human invasion in wildlife areas, subsequently leading to an increased passage of animals towards human dwellings and more exposure to animals, making humans susceptible to these infections. Climate change is another major factor. Global warming and the evolving thermotolerance of fungi, adapting more to human body temperature than their saprophytic nature, is leading to the emergence of humans as new hosts for fungi. The domestication of animals, rising populations, enhanced tourism, migratory populations, intrusions into wildlife, etc., are other known factors. Zoonotic fungal infections have long been neglected and are now gaining due attention. In this review, we briefly discuss the various aspects currently known for zoonotic fungal infections and bring forth the importance of this particular issue to be addressed in a timely manner.